Correlation Study of Insulin Resistance and Essential Hypertension among Bangladeshi Male Volunteers - Mainul, Haque; Susmita, Sinha; Qazi Shamima, Akhter (2015)
Background: The patients with essential hypertension are increasing all over the world. There may be development of insulin resistance and hyperinsulinemia in essential hypertension. An association between essential hypertension and defective insulin secretion has been identified. Insulin resistance is the fundamental defect in the development of type 2 diabetes mellitus, hypertension and cardiovascular diseases. Objective: To observe the insulin resistance in adult male with essential hypertension. Methods: This is a cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, Bangladesh from July 2012 to June 2013. A total number of 150 male subjects were selected with age ranging from 25-45 years. Seventy five male essential hypertensives were enrolled from Out- patient Department of Medicine, Dhaka Medical College Hospital, Dhaka. Otherwise healthy 75 of similar age were studied as control. Insulin resistance was assessed by HOMA-IR method. Fasting serum insulin level was measured by ELISA and fasting blood glucose by glucose oxidase method. Unpaired Student’s ‘t’ and Pearson’s correlation coefficient (r) tests were performed for statistical analyses. Results: Current study reveals that essential hypertension has positive and significant relationship with fasting serum insulin level and insulin resistance. Conclusion: Incidence of insulin resistance is higher in essential hypertensive subjects in comparison to the control subjects. More in-depth prospective research is advocated to find remedies for common Bangladeshi patients.